The Development of Three - Dimensions Animation for Instructional Media in Biology: Kingdom Animalia : Phylum Platyhelminthes and Phylum Nematoda - Punyarat Punya; Narathorn Pramuanrattakarn (วารสารวิทยาการสารสนเทศและเทคโนโลยีประยุกต์, 2018)
The aim of this research is to 1) develop a three-dimensions animation for instructional media in Biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda". 2) Study the perception of the sample audience to use three-dimensions animation for instructional media in Biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda". 3) Study the level of satisfaction of the sample audience to using three-dimensions animation for instructional media in Biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda". The sample was consisted of 72 students in the senior high school during the first semester of academic year 2017 at Korat Pittayakom School, Nakhon Ratchasima, Thailand. The tools used to collect data were: 1) Three-dimensions animation for instructional media in Biology : kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda". 2) Three-dimensions animation for instructional media in biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda" quality assessment by experts. 3) Assessment form of the sample using three-dimensions animation for instructional media in biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda". 4) Satisfaction assessment form of the sample using three-dimensions animation for instructional media in Biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda". The statistics used in this study were average, standard deviation and percentage. The research found that 1) Quality of three-dimensions animation for instructional media in Biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda" overall at the average was 4.02, quality is good. 2) Perception of the sample from using three-dimensions animation for instructional media in Biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda" overall of perception was 83.47 percent, the perception at the highest level. 3) Satisfaction of the sample from using three-dimensions animation for instructional media in Biology : Kingdom Animalia "Phylum Platyhelminthes and Phylum Nematoda", overall statisfied at the average was 4.17, satisfaction was at a high level.